Effect of Enterococcus hirae GS22 Fermentation-Assisted Extraction on the Physicochemical and Bioactivities of Sea Cucumber Intestinal Polysaccharides - Xiqian Tan; Xiaoqing Wang; Fangchao Cui; Ali Zeshan; Dangfeng Wang; Xuepeng Li; Jianrong Li (Molecules)
The sea cucumber intestine (SI), a secondary product from sea cucumber processing, contains polysaccharides as one of its active ingredients, and fermentation is an effective method for extracting bioactive substances from food by-products. In this study, to explore the effect of Enterococcus hirae GS22 fermentation on the extraction of SI polysaccharides, the polysaccharides were extracted through the SI with and without Enterococcus hirae GS22 fermentation, and the obtained polysaccharides were designated as SC-PF and SC-P. The extraction yield, the structural characteristics, and the biological functions of the polysaccharides were then evaluated. The results indicated that Enterococcus hirae GS22 could grow well using SI as the substrate and that fermentation could improve the extraction yield of the polysaccharide from 0.48% to 0.63%, decrease the molecular weight (Mw), and change the monosaccharide composition. The diameter of SC-PF was smaller than SC-P, and the absolute value of the zeta potential of SC-PF was found to be lower than SC-P. Fermentation does not change the functional group or the thermal ability of the polysaccharide. SC-PF had better antioxidant ability than SC-P; the DPPH and superoxide anion scavenging ability were 96.3% and 36.5%, respectively. SC-PF also showed nearly 1.3- and 1.1-fold higher inhibition of α-glucosidase and α-amylase as compared to SC-P. The current results showed that E. hirae GS22 fermentation has the potential to extract SI polysaccharides with better prebiotic abilities.